Age-specific impact of COVID-19 on birth rates in Japan: An interrupted time-series analysis using national vital statistics - Tasuku Okui (PLoS ONE, 2026)
Objectives A study investigating the impact of COVID-19 on birth rates across women’s age groups has not been previously conducted in Japan. Therefore, we examined this issue using national birth data. Methods The analysis utilized monthly live birth data from the Vital Statistics from 2015 to 2023, which were accessed on July 27, 2025. We estimated the expected number of births in the post-pandemic period through quasi-Poisson regression analysis and calculated the ratios of the sum of actual births to that of predicted births for each women’s age group. In addition, a segmented regression analysis was performed to assess the effect of the pandemic on birth rates, focusing on changes in level and trend across age groups. Results The ratios of the sum of actual births to that of predicted births in the post-pandemic period was close to one overall, but actual numbers were significantly lower than predicted numbers in women aged 15–19, 20–24, 25–29, and 35–39 years. Segmented regression analysis revealed significant declines in birth rates among women aged 15–19, 20–24, and 45–49 years due to the pandemic, with the rate ratios (RRs) being 0.880 (95% confidence interval (CI): 0.828, 0.935), 0.936 (95%CI: 0.907, 0.967), and 0.890 (95%CI: 0.824, 0.961), respectively, indicating that an immediate effect of the pandemic was evident in those age groups. In addition, significant trend changes were observed among women aged 20–24, 25–29, 35–39, and 45–49 years, with the RRs being 0.995 (95%CI: 0.993, 0.996), 0.998 (95%CI: 0.996, 0.999), 0.998 (95%CI: 0.997, 1.000), and 1.004 (95%CI: 1.001, 1.008), respectively, indicating an acceleration of the declining trend in some age groups. Conclusions These findings suggest that the pandemic’s effect on birth rates varies by women’s age, with a more pronounced decrease among younger women.